Membangun Dialog Peradaban - Zaprulkhan, Zaprulkhan (Edugama: Jurnal Kependidikan dan Sosial Keagamaan, 2017)
Abstract: In 1989 Francis Fukuyama with his article The End of History? In the journal The National Interest revolves a speculative thesis that after the West conquered its ideological rival, hereditary monarchy, fascism and communism, the constellation of the world of international politics reached a remarkable consensus to liberal democracy. A few years later, Samuel P. Huntington came up with a more provocative thesis that ideological-based war would be a civilization-based war in his article, The Clash of Civilizations? In the journal Foreign Affairs. It reveals that in the future the world will be shaped by interactions among the seven or eight major civilizations of Western civilization: Confucius, Japan, Islam, Hinduism, Orthodox Slavs, Latin America and possibly Africa. Huntington directed the West to pay particular attention to Islam, for Islam is the only civilization with great potential to shake Western civilization. Departing from the above hypotheses, this paper will specifically discuss the bias of Fukuyama and Huntington's thesis on Islam, and how its solution to build a dialogue of civilization by taking the paradigm of dialogue from Ibn Rushd and Raghib As-Sirjani. Abstrak: Pada tahun 1989 Francis Fukuyama dengan artikelnya The End of History? Dalam jurnal The National Interest revolusioner tesis spekulatif bahwa setelah Barat telah menaklukkan lawan-lawan ideologisnya, monarki herediter, fasisme dan komunisme, konstelasi politik internasional mencapai konsensus yang luar biasa untuk demokrasi liberal. Beberapa tahun kemudian, Samuel P. Huntington muncul dengan tesis yang lebih provokatif bahwa perang berbasis ideologis akan menjadi perang berbasis peradaban dalam artikelnya, The Clash of Civilisations? Dalam jurnal Luar Negeri. Ini mengungkapkan bahwa di masa depan akan dibentuk oleh interaksi antara tujuh atau delapan peradaban utama peradaban Barat: Konfusius, Jepang, Islam, Hindu, Slavia Ortodoks, Amerika Latin dan mungkin Afrika. Perhatian Huntington pada Islam adalah potensi terpenting untuk mengguncang peradaban Barat. Berangkat dari hipotesis di atas, makalah ini akan secara khusus membahas bias tesis Fukuyama dan Huntington tentang Islam, dan bagaimana mereka akan mengambil paradigma dialog dari Ibn Rushd dan Raghib As-Sirjani.